ANESTHESIA MANAGEMENT FOR PATIENTS WITH LOW EJECTION FRACTION UNDERGOING CORONARY ARTERY BYPASS GRAFTING (CABG) - Wibowo, Adi; Pratomo, Bhirowo Yudho (Fakultas Kedokteran Universitas Jenderal Soedirman, 2024)
Background: Coronary Artery Disease (CAD) is a condition caused by the formation of blockages in the coronary blood vessels. The primary non-invasive procedure for CAD patients is Percutaneous Coronary Intervention (PCI). However, complications during PCI, such as unstable hemodynamic arrhythmias, can occur, possibly due to Abrupt Vessel Closure (AVC). This remains a major issue for PCI failure and necessitating Coronary Artery Bypass Grafting (CABG). Case: We report a 68-year-old male patient with CAD and total occlusion of the Right Coronary Artery (RCA) and total occlusion of the Left Circumflex (LCx) who was unable to undergo PCI at a previous hospital. Subsequently, re-catheterization at RSUP Dr. Sardjito, CAD3VD was diagnosed, leading to a planned CABG surgery. The patient’s clinical condition was relatively stable, though he had a low ejection fraction (41%). Induction, invasive monitoring placement, and intubation proceeded smoothly. CABG was performed with three grafts (LIMA-LAD, SVG-OM, SVG-PDA), and successful weaning was achieved with dobutamine support. The patient was in the ICU for 2 days for clinical and hemodynamic optimization before being transferred to the ICCU for further intensive care. Discussion: The main principle of anesthetic management in this case is to maintain a balance between myocardial oxygen supply and demand. Strict monitoring of hemodynamic changes during surgery is essential to guide necessary supportive therapy. Patients with low ejection fractions are at high risk for post-operative mortality and complications. Post-operative management in the ICU focuses on optimizing clinical condition and addressing any emerging potential issues. Conclusion: Surgery for patients with CABG requires complicated and complex anesthetic techniques. This operation requires collaboration and good communication between the surgeon and the anesthesiologist.